Bilmecelerin Dil-Düşünme Bağlamında Eğitimdeki Yeri ve Önemi The Place and Importance of Riddles in the Context of Language and Thinking - Elif Emine, BALTA (ASOS Eğitim Bilişim Danışmanlık, 2018)
Riddles, the entertaining works of folk literature with simple appearances (structures), deep backgrounds and artistic expressions, also have the moral value of carrying the centuries of accumulated cultural traces into today. In daily life, riddle has lost its old popularity.This is quite normal. Because changes in life conditions, variations inthe quality of social environments, individualization and similar reasonshave altered the interests and pleasures of people as well as their needsand understandings.In academic context, studies on riddles have been limited with thefield of folklore. The valuable studies done on this field have not beensufficiently evaluated within the scope of education and teaching.Today, it is seen that, riddles do not take place within framework ofeducation and teaching. However, riddles have richness and deepnessthat can be used as a means of reaching success in not merely teachinglanguage and concepts but also in closely related thought. The biggestcontribution of riddles to the education and teaching process is seen innative language education. Riddles can be seen as a means of teachingconcepts and enriching word treasure. In a riddle, the process ofsearching answer is dynamic; that is, one compares all the conceptspassing through his mind with the features given in the question.“Clearly, riddles correlate with high order thinking like creativethinking, critical thinking and problem solving. So riddles must beappreciated educational and intellectual context and included ineducation and teaching environments”. In this study, the place andsignificance of riddle as an effective tool and a rich stimulant ineducation and teaching will be determined and explained. Bilmeceler, sade görünümleri, derin arka planları ve sanatlı söyleyişleri ile eğlenceli halk edebiyatı ürünleri olup yüzyıllar boyu, biriktirmiş olduğu kültürel ögeleri günümüze taşıma gibi manevi değere sahiptir. Gündelik hayatta bilmeceler, eski popülerliğini kaybetmiştir. Yaşam koşullarının farklılaşması, sosyal ortamların niteliğini değişmesi, bireyselleşme ve benzer sebepler, insanların ihtiyaçları ve anlayışlarında olduğu gibi ilgi ve zevklerini de değiştirdiği için bu durum normal karşılanabilir.Akademik anlamda, bilmeceler ile ilgili çalışmalar halkbilim sahasında sınırlı kalmıştır. Bu sahada yapılmış olan değerli çalışmalar ise eğitim-öğretim boyutunda yeteri kadar değerlendirilmemiştir. Eğitim öğretim alanında da bilmecelere yeteri kadar yer verilmediği görülmektedir. Oysa bilmeceler, dil ve kavram öğretiminde, bunlarla yakından ilişkili olan düşünme öğretiminde de başarı sağlamada araç olarak kullanılabilecek zenginlik ve derinlik özelliğine sahiptir. Eğitim-öğretim sürecinde, bilmecelerin en önemli katkısı, anadili eğitiminde görülür. Kavram öğretiminde ve kelime hazinesini zenginleştirmede bilmeceler yardımcı araç olarak görülebilir. Bilmecede cevabı arama süreci dinamiktir; birey, zihninden geçen tüm kavramları soruda belirtilen özellikleri ile karşılaştırır. Açık bir ifadeyle bilmeceler üst düzey düşünme becerilerinden olan yaratıcı düşünme, eleştirel düşünme ve problem çözme becerileri ile ilişkilidir. Bilmecelerin eğitsel ve düşünsel bağlamda değerinin farkına varılmalı ve diğer edebi türler gibi eğitim ortamlarına dahil edilmelidir. Bu çalışmada, bilmece türünün eğitim-öğretimde etkili bir araç, zengin bir uyaran olarak yeri ve önemi belirlenmiş ve açıklanmıştır.